The tranexamic acid: as chemical tourniquet during Ward-Mayo’s operation - Mandal, Sarbeswar; Mondal, Sumanta Kumar; Pathak, Pragati Awasthi; Agarwal, Kavita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2020)
Background: The intra-operative blood loss which required transfusion is one of the complications in Ward-Mayo’s operation. The objective of this study was to evaluate its effectiveness to minimizes hemorrhage in Ward-Mayo’s operation Methods: It is a well-designed, Clinical, interventional, prospective, randomized control trial. In the department of obstetrics and gynecology, IPGMER-SSKM (PG) H, Kolkata, West Bengal, India. More than one-year study. After ethics approval, the total number of sixty-six cases will be selected with randomization for Ward-Mayo operation and allocated into two groups operated as - Gr-A (n = 33 cases) - by infiltrating locally tranexaminic acid, Gr-B (n = 33-controls) - application local conventional haemostatics. Results: The outcome informs of primary and secondary assessed, analyzed, tabulated and statistically significant showed accordingly as per graph pad software. In Table 1 and 2. The results of individual group (Gr. A and Gr. B) in forms of pry and Sec. outcomes showed that there are better outcomes in all aspects with zero mortality Tranexamic group than controls. Conclusions: This study concluded that the Tranexamic Acid can safely and effectively used by local infiltration during Ward-Mayo’ operation. Like other department, this technique can be utilized in other vaginal procedure (ex-Episiotomy).